Makna Judul The Good Bad Mother: Sebuah Kajian Semiotika Roland Barthes - Azhari, Diazti Salsabila; Fadillah, Dani (Jurnal Audiens, 2025)
The title of an audiovisual work serves not only as an identity but also as an initial representation of the theme, conflict, and message being conveyed. This study aims to analyze the meaning of the title "The Good Bad Mother" (2023) using Roland Barthes's semiotic theory, which distinguishes between denotative, connotative, and mythical meanings. This study employed a qualitative method with a descriptive-analytical approach. Data were collected from key scenes in the drama and analyzed based on the structure of signs: signifier and signified. The results show that the meanings of "good" and "bad" in the context of motherhood are relative and dependent on cultural constructions. This title represents the complexity of a mother's role, which is not only gentle and loving, but also firm and even painful for the sake of her child. Through Barthes's semiotic analysis, this study reveals that the title "The Good Bad Mother" is a cultural sign that debunks the myth of ideal motherhood and challenges the normative interpretation of the mother's role in society.